The Role and Responsibility of the Government in Protecting the Rights of Electronic Certificate Holders in Accordance with the Principle of Legal Protection - Asmorowati, Meiti (Intellectual Law Review (ILRE), 2025)
This study aims to analyse the role and responsibility of the government in providing legal protection for holders of electronic certificates (e-certificates), particularly in ensuring legal certainty and data security in accordance with the mandate of Article 28D of the 1945 Constitution. This study uses a normative juridical method with a statute approach and a conceptual approach. Data analysis was conducted qualitatively and descriptively on secondary data covering primary, secondary, and tertiary legal materials. The results of the study show that although a formal legal basis exists (ITE Law, Government Regulation No. 18/2021, and ATR/BPN Ministerial Regulation No. 3/2023) that provides a framework for preventive and repressive protection, its implementation still faces crucial problems. These problems include: (1) uneven infrastructure and human resource readiness, which risks violating the principles of legal certainty and equal protection; (2) a legal culture gap or public doubt regarding the validity of electronic documents; (3) inconsistency and fragmentation of implementing regulations, giving rise to multiple interpretations; and (4) a lack of clear norms regarding state accountability mechanisms, compensation, and restoration of rights in the event of system failure or data leaks.